2014
DOI: 10.1185/03007995.2014.884492
|View full text |Cite
|
Sign up to set email alerts
|

COPD management according to old and new GOLD guidelines: an observational study with Italian general practitioners

Abstract: Guideline recommendations are applied only partially within clinical practice. A higher prescriptive appropriateness is shown by GPs using nGOLD classification. This might be due to the fact that nGOLD, with respect to oGOLD, takes into account anamnestic usual features considered by GPs in their clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
7
14
0
1
Order By: Relevance
“…To verify the sample's representativeness, we could confirm that the spectrum of bronchial obstruction severity (GOLD 1, 2, 3, 4) among the patients in the study closely resembled that of the COPD population, as officially reported [36]. As in a study recently conducted in Italy, the majority of patients in our study suffered from moderate COPD (46% vs. 51.5% in Italy), and belonged to the D category (43.7% objectively classified patients vs. 45.6% in Italy) [37].…”
Section: Discussionsupporting
confidence: 87%
“…To verify the sample's representativeness, we could confirm that the spectrum of bronchial obstruction severity (GOLD 1, 2, 3, 4) among the patients in the study closely resembled that of the COPD population, as officially reported [36]. As in a study recently conducted in Italy, the majority of patients in our study suffered from moderate COPD (46% vs. 51.5% in Italy), and belonged to the D category (43.7% objectively classified patients vs. 45.6% in Italy) [37].…”
Section: Discussionsupporting
confidence: 87%
“…The overall finding of this study—that the prescribing of long‐acting bronchodilators and ICSs in patients with COPD does not appear to align with GOLD guidelines—is consistent with recent studies based on subgroups of patients in a variety of settings. Our observation that the most commonly dispensed first regimen involving a long‐acting bronchodilator was a LABA in combination with an ICS is consistent with findings from Spain, the Netherlands and some, but not all, studies based in the UK.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies in diverse settings have found that prescribing practice does not conform to international or national COPD treatment guidelines, or drug licencing conditions. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, these investigations have been based on subgroups of patients drawn from selected general practices, health insurance databases, or respiratory outpatient clinics or hospitals, and none have examined the longitudinal patterns of use of long-acting bronchodilator therapy in new users across an entire country.…”
Section: Summary At a Glancementioning
confidence: 99%
“…Previous studies have mainly investigated resources,12–14,16 and the identification of underutilization is very important. The finding is consistent with an Italian study of COPD management where general practitioners stated that 13% of patients were referred to pulmonary rehabilitation in29 and with a Swiss study of patients referred to hospitals due to exacerbation, where 27% had participated in pulmonary rehabilitation 30. Suggested reasons for barriers to rehabilitation are lack of awareness of pulmonary rehabilitation in both patients and health care professionals, low access, low perceived health benefits, and comorbidity 31.…”
Section: Discussionsupporting
confidence: 89%